“Could you please…” vs. “Tayyorlang”: A pragmatic investigation of indirectness and directness in English and Uzbek language orders - Kuchkarova, Maftuna (The Lingua Spectrum, 2025)
This research article investigates the pragmatic tactics used to articulate direct and indirect orders in the English and Uzbek linguistic environments, with a focus on educational leadership settings. This study uses frameworks based on speech act theory and politeness theory to analyse how cultural norms impact the expression of instructions in these two typologically dissimilar languages (Austin, 1962; Searle, 1975; Brown & Levinson, 1987). According to the findings, English speakers generally attenuate their directions via modal verbs, hedging, and collaborative framing approaches. In contrast, Uzbek speakers prefer more direct imperative formulations that are shaped by established social hierarchies and role-based expectations. The approach, which uses real speech samples, shows how the concept of politeness is encoded and culturally defined in directive communication (Thomas, 1983). Furthermore, the study emphasizes how language users adopt either linguistic softening or hierarchical positioning depending on their communicative roles and contexts. This work contributes significantly to the subject of intercultural pragmatics and has implications for educators and institutional leaders dealing with complicated multilingual or multicultural situations. The insights gathered may aid in more nuanced and courteous communication across various institutional contexts.